(untitled) (Research, Society and Development, 2021)
The physiographic characteristics of the landscape are essential information for the planning and management of water resources in the microbasins. The objective was to analyze the morphometry and soil cover dynamics in the Pirarara microbasin, Amazonia, Brazil. Geometry, relief and drainage were analyzed using images from the Alos satellites, and deforestation (NDVI) whit images from the Landsat 5 and 8 satellites (1988 to 2018), using QGIS and Google Earth softwares. The microbasin has low susceptibility to floods, flat to mountainous reliefs, complex drainage and 73.86% of the deforested area. The microbasin was largely affected by the migratory and agricultural expansion in the State.